2016
DOI: 10.1007/s11548-016-1433-0
|View full text |Cite
|
Sign up to set email alerts
|

Automatic thalamus and hippocampus segmentation from MP2RAGE: comparison of publicly available methods and implications for DTI quantification

Abstract: Overall we find that volBrain is superior in thalamus and hippocampus segmentation compared to FSL, FreeSurfer and SPM. Furthermore, the choice of segmentation technique and training library affects quantitative results from diffusivity measures in thalamus and hippocampus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 25 publications
2
43
0
1
Order By: Relevance
“…Manual delineations from HHP (Boccardi et al, 2015), representing state-of-the-art in manual hippocampus segmentation, were used as expert priors (Anker, 2014, Anker et al, 2014). The method has previously demonstrated a better atrophy-based AD diagnostic performance than static FreeSurfer (Anker et al, 2014), and have in recent comparison studies performed by other research groups demonstrated better correspondence with manual segmentations than FreeSurfer (Manjón and Coupé, 2016, Næss-Schmidt et al, 2016). …”
Section: Methodsmentioning
confidence: 96%
“…Manual delineations from HHP (Boccardi et al, 2015), representing state-of-the-art in manual hippocampus segmentation, were used as expert priors (Anker, 2014, Anker et al, 2014). The method has previously demonstrated a better atrophy-based AD diagnostic performance than static FreeSurfer (Anker et al, 2014), and have in recent comparison studies performed by other research groups demonstrated better correspondence with manual segmentations than FreeSurfer (Manjón and Coupé, 2016, Næss-Schmidt et al, 2016). …”
Section: Methodsmentioning
confidence: 96%
“…Previous studies have explored segmentation of MP2RAGE using traditional software packages as well as customized algorithms . Although some promising results were shown, there are still some unresolved issues.…”
Section: Discussionmentioning
confidence: 99%
“…A complex ratio of the two volumes was used to generate uniform T 1 ‐weighted images and quantitative T 1 maps insensitive to B 1 field inhomogeneity . A few studies have explored brain segmentation of the uniform T 1 ‐weighted images using both conventional segmentation tools and customized methods for MP2RAGE . Although most existing segmentation methods are mainly optimized for conventional T 1 ‐weighted images, some studies showed promising segmentation performance using MP2RAGE compared to using MPRAGE with commonly used softwares .…”
mentioning
confidence: 99%
“…compared the performances of publicly available segmentation tools (volBrain, FSL, FreeSurfer and SPM) and their impact on diffusion quantification, emphasizing the importance of using recently developed segmentation algorithms and imaging techniques. They found that volBrain is superior in thalamus and hippocampus segmentation compared to FSL, FreeSurfer and SPM 3 . Shape is important information for brain structure segmentation.…”
Section: Introductionmentioning
confidence: 99%